Germline and Somatic Mutations in Homologous Recombination Genes Predict Platinum Response and Survival in Ovarian, Fallopian Tube, and Peritoneal Carcinomas - Pennington, Kathryn P.; Walsh, Tom; Harrell, Maria I.; Lee, Ming K.; Pennil, Christopher C.; Rendi, Mara H.; Thornton, Anne; Norquist, Barbara M.; Casadei, Silvia; Nord, Alexander S.; Agnew, Kathy J.; Pritchard, Colin C.; et al. (Clinical cancer research, 2014)
Purpose: Hallmarks of germline BRCA1/2-associated ovarian carcinomas include chemosensitivity and improved survival. The therapeutic impact of somatic BRCA1/2 mutations and mutations in other homologous recombination DNA repair genes is uncertain. Experimental Design: Using targeted capture and massively parallel genomic sequencing, we assessed 390 ovarian carcinomas for germline and somatic loss-of-function mutations in 30 genes, including BRCA1, BRCA2, and 11 other genes in the homologous recombination pathway. Results: Thirty-one percent of ovarian carcinomas had a deleterious germline (24%) and/or somatic (9%) mutation in one or more of the 13 homologous recombination genes: BRCA1, BRCA2, ATM, BARD1, BRIP1, CHEK1, CHEK2, FAM175A, MRE11A, NBN, PALB2, RAD51C, and RAD51D. Nonserous ovarian carcinomas had similar rates of homologous recombination mutations to serous carcinomas (28% vs. 31%, P = 0.6), including clear cell, endometrioid, and carcinosarcoma. The presence of germline and somatic homologous recombination mutations was highly predictive of primary platinum sensitivity (P = 0.0002) and improved overall survival (P = 0.0006), with a median overall survival of 66 months in germline homologous recombination mutation carriers, 59 months in cases with a somatic homologous recombination mutation, and 41 months for cases without a homologous recombination mutation. Conclusions: Germline or somatic mutations in homologous recombination genes are present in almost one third of ovarian carcinomas, including both serous and nonserous histologies. Somatic BRCA1/2 mutations and mutations in other homologous recombination genes have a similar positive impact on overall survival and platinum responsiveness as germline BRCA1/2 mutations. The similar rate of homologous recombination mutations in nonserous carcinomas supports their inclusion in PARP inhibitor clinical trials. Clin Cancer Res; 20(3); 764–75. ©2013 AACR.